2015
DOI: 10.1002/cbin.10512
|View full text |Cite
|
Sign up to set email alerts
|

Microautophagy involves programmed cell semi‐death of sieve elements in developing caryopsis of Triticum aestivum L.

Abstract: Differentiation of sieve elements (SEs) involves programmed cell semi-death, in which a small amount of organelles is retained. However, the mechanisms by which a large amount of SE cytoplasm is degraded and the specific proteases involved are not clear. In this study, we confirmed that the degradation of cytoplasm outside of the vacuole was mediated by microautophagy of the vacuole, and that the tonoplast selectively fused with the plasma membrane after most of the cytoplasm in the vacuoles was degraded. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…A selective autophagy-like process, similar to microautophagy, is functionally involved in the formation of phloem SEs in the developing caryopsis in wheat (Wang et al 2008 ). The process pertaining to the partial degradation of cytoplasmic material in SEs is even referred to as ‘programmed cell semi-death’ (Yang et al 2015 ). Within the developing caryopsis of wheat, the central vacuole and cytosol of differentiating phloem cells were found to become weakly acidified after rupture of the tonoplast (Yang et al 2015 ).…”
Section: Autophagy During Root Ontogenymentioning
confidence: 99%
See 2 more Smart Citations
“…A selective autophagy-like process, similar to microautophagy, is functionally involved in the formation of phloem SEs in the developing caryopsis in wheat (Wang et al 2008 ). The process pertaining to the partial degradation of cytoplasmic material in SEs is even referred to as ‘programmed cell semi-death’ (Yang et al 2015 ). Within the developing caryopsis of wheat, the central vacuole and cytosol of differentiating phloem cells were found to become weakly acidified after rupture of the tonoplast (Yang et al 2015 ).…”
Section: Autophagy During Root Ontogenymentioning
confidence: 99%
“…The process pertaining to the partial degradation of cytoplasmic material in SEs is even referred to as ‘programmed cell semi-death’ (Yang et al 2015 ). Within the developing caryopsis of wheat, the central vacuole and cytosol of differentiating phloem cells were found to become weakly acidified after rupture of the tonoplast (Yang et al 2015 ). It is plausible that two potential degradation pathways exist; one that involves the function of the endoplasmic reticulum (ER) for the selective envelopment of organelles; and the other putative pathway involves selective inclusion into vacuoles (Wang et al 2008 ).…”
Section: Autophagy During Root Ontogenymentioning
confidence: 99%
See 1 more Smart Citation
“…During several tissue development, autophagy can be engaged in proper vacuole biogenesis (Inoue et al 2006;Yano et al 2007). It occurs constitutively during formation of both cortical tissue (Yano et al 2007) and sieve elements of phloem (Yang et al 2015), but does not lead to cell death. The dual nature of autophagy causes on one hand the appropriate functioning of every living plant cell, but on the other hand it is also involved in initiating a program of cellular degradation during programmed cell death (PCD).…”
Section: Introductionmentioning
confidence: 99%
“…The most relevant studies of autophagy during development concern xylogenesis, where structural and biochemical evidence of the role of dPCD in tracheary formation have been provided in Zinnia elegans suspension cultures that were forced to transdifferentiate into tracheary elements (Fukuda et al 1993(Fukuda et al , 1998Fukuda 1996Fukuda , 2000Fukuda , 2004Kuriyama and Fukuda 2006) and later confirmed in planta for Arabidopsis (Avci et al 2008;Kwon et al 2010) and Populus (Courtois-Moreau et al 2009;Bagniewska-Zadworna et al 2012, 2014a. Only few studies on programmed cell semi-death of phloem sieve cells were performed in developing caryopsis of Titicum aestivum, indicating that selective autophagy can be involved in that developmental process which does not end with cell death (Wang et al 2008;Yang et al 2015). Other studies of the role of dPCD have been conducted in relation to leaf morphogenesis (Gunawardena et al 2004;Wertman et al 2012), male reproductive development in plants (Hanamata et al 2014), and plant embryogenesis (Bozhkov et al 2005;Di Berardino et al 2018).…”
Section: Introductionmentioning
confidence: 99%